PERBANDINGAN TIGA ALGORITMA CLASSIFIER UNTUK PENENTUAN PENERIMAAN PESERTA DIDIK BARU PADA SEKOLAH MENENGAH ATAS - Yulhendri; Kundang Karsono Juman (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2021)
ABSTRAK New Student Admissions (PPDB) have been carried out since the 2012/2013 school year by schools that have been verified by the Ministry of Education. From the 2012/2013 school year to the 2018/2019 school year, 1279 schools have been registered and verified. The activity of accepting new students (PPDB) for SMA is not an independent one, but is not separated from various aspects. Education staff, participants, schools, school quotas, and participant scores. And one of the most important processes of new student admissions is the prediction of the selection of high school schools. The problem faced by prospective students is prediction for school selection. The predictions made so far have only focused on the passing grade of each school. However, the passing grade that is focused on only revolves around the previous year. Therefore, we need a system to predict participants in choosing schools from new student admissions activities by implementing several machine learning algorithms. Keywords: Machine Learning, Prediction, PPDB High School. Abstrak Penerimaan Peserta Didik Baru Baru (PPDB) sudah dilakukan sejak tahun ajaran 2012/2013 oleh sekolah yang sudah diverivikasi oleh Departemen Pendidikan. Dari tahun ajar 2012/2013 sampai tahun ajar 2018/2019 sudah 1279 sekolah yang sudah terdaftar dan sudah diverivikasi. Kegiatan Penirimaan peserta didik baru (PPDB) SMA bukan yang berdiri sendiri, namun tidak dipisahkan dari ber-bagai aspek. Tenanga penddika, peserta, sekolah, kuota sekolah, dan nilai peserta. Dan salah satu proses yang terpenting dari kegiatan penerimaan peserta didik baru adalah prediksi pemilihan sekolah SMA. Masalah yang dihadapi oleh para calon siswa adalah prediksi untuk pemilihan sekolah. Prediksi yang dilakukan sampai sekarang hanya terfokus pada passing grade setiap sekolah. Akan tetapi, passing grade yang di fokuskan hanya berkisar di tahun sebelum nya. Oleh karena itu, di butuhkan sebuah sistem untuk memprediksikan peserta dalam memilih sekolah dari kegiatan penerimaan peserta didik baru dengan mengimplementasi dari Beberapa Algoritma Machine Learning. Kata Kunci: Machine Learning, Prediksi, PPDB SMA.